DELAYED DIAGNOSIS OF SEVERE OSTEOMALACIA IN A PATIENT WITH RTA - S, Tivya; HR, Ijaz; AR, Anilah (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION A 37-year-old lady was admitted to the medical ward for complaints of worsening body and muscle weakness and generalized bony pain for the past 4 years following a minor motor vehicle accident causing significant debility and disability. She was diagnosed with RTA in 1999 complicated by nephrocalcinosis however had defaulted follow up and medications. Her sister was also diagnosed with RTA albeit with milder symptoms. CASE Clinical examination revealed generalized proximal muscle weakness with no focal neurological signs or cranial nerve deficits. Biochemical investigations revealed normal anion metabolic acidosis, hypokalemia (K 2.5 mmol/l), hypophosphatemia (PO4 0.49 mmol/L), normal corrected calcium of 2.20 mmol/L, a high ALP level of 549 IU/L and a normal PTH level of 19.6 pg/ml. The Fractional excretion of phosphate was elevated at 21.09% suggestive of urinary phosphate wasting with no hypercalciuria. Vitamin D level (25 OH Vitamin D) was low at 10 nmol/L. Radiographs of the extremities and pelvis done showed multiple looser zones at the right scapula, pelvic rami and right neck of femur. A BMD scan revealed a Total T score of -4.0 and -3.5 at the hip and spine respectively. Nerve conduction study done during the admission was suggestive of chronic myopathy of systemic disease. A diagnosis of severe osteomalacia secondary to RTA with coexistent Vitamin D deficiency was made. The patient was started on high dose Vitamin D, Shohl's solution with potassium supplementation and was referred for rehabilitation and physiotherapy. CONCLUSION Phosphate levels normalized and repeated Vitamin D level improved to 29 nmol/L and the patients pain and muscle power has significantly improved since then. A BMD scan is planned in a year to reassess response to therapy.